Teknik Penyusunan Modul Materi Sistem Ekkresi dengan Model Problem Based Learning Biologi SMA - Eka vasia anggis (Universitas Sebelas Maret, 2017)
The Purposed of this research as follow: 1) Tecnical arrangement human excretion system in modul based contructivism with problem based learning in Biology SMA; 2) Validating human excretion system modul based contructivism with problem based learning in Biology SMA Laboratorium. This research methode is reserach and development with the steps that been adjusted with researcher needs as follow: 1) Define step, 2). Design step, 3) Develop step. This research still how to arrange modul based PBL that use human excretion system topic in Senior High School. Location of research is in Senior High School Laboratorium Malang. This result research, such is steps of technical arrangement modul based PBL by excretion system, percentage average of modul feasibility by lecturer of learning material expert lecturer of material expert biology, and teacher in the grade natural science-3 have feasibility. This is important to development modul before implementation in field